LEGAL PERPSECTIVE ON THE TRADE FACILITATION AGREEMENT (TFA): INDONESIA CASE STUDIES - Ersya, Ozy Diva (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
he application of trade facilitation needs further analyses in the context of Indonesian’s law. So far Indonesia does not yet ratify the trade facilitation agreement. In one hand the trade facilitation is a compulsory requirement that must be fulfilled by a state, in other hands the state does not provide a legal instrument. The consequence is legal uncertainty to those parties who want to invest their money in Indonesia. The trade facilitation will also in line with ASEAN programs. Those programs have same purposes to fasten the movement of goods and services by providing legal certainty on trade facilitation foundations. The WTO TFA can be used as ‘soft-law’ for Indonesian legal framework to apply trade facilitation enhancement, although it is not yet ratified by Indonesia. The WTO TFA will easily appropriate and have legal force if the implementation of the WTO TFA into Indonesian national legal structure is also noticeable.